TYPOLOGY OF CAR GLASS FILM TOWARDS CLIMATE IN ANTICIPATION TO GLOBAL WARMING - Irsan, Robby; Fitrianingsih, Yulisa; Soeryamassoeka, SB. (Jurnal Teknik Sipil, 2022)
Climate change has a significant impact on the socio-economic and development of Indonesia. Transportation in this study is related to cars where cars require a lot of fuel consumption. Window Film is able to reject Infrared from sunlight which ensures that the car cabin will feel cooler can help overcome climate change. This study explains how the right type and and the percentage of window are used in the tropics to deal with global climate change. The purpose of this study was to analyze the parameters of temperature, wind speed, lighting, and noise originating from the outside of the car on the ability of each type of car window film to reduce heat. The research method used is the method of collecting data by taking data on the characteristics of temperature, lighting, wind speed and noise inside the car and outside the car which affect the window film. The results of scoring the noise quality standard using the application from SPSS using Crosstab, the quality standard is at a Moderate level between 56-65 db(A), the quality standard lighting level is at a Moderate level between 500-999 Lux, the wind speed to humans is at a very high level. The average score between Effective Temperature and Minimum Humidityis 24.46 °C with 63% Humidity. Typology of 40% window film with a combination of glasswall dampers is able to reduce the value of climate parameters from outside the car.